The Pericing Of Initial Public Offerings And Subsequent Dividend Behavior: Evidence From Bursa Malaysia - Montazeri, Seyed Mehdi (2008)
This study investigates the pricing performance of Initial Public offerings (IPOs0 of Main Board and MESDAQ Board of Bursa Malaysia during 2005 to 2007. This study investigates the Dividend behavior of the companies listed on Main Board and MESDAQ Board during this period which have paid dividend in the year 2008.